Development of Women Entrepreneurship Research in Global Perspective through Bibliometric Study - Judijanto, Loso (West Science Journal Economic and Entrepreneurship, 2025)
Women entrepreneurship has increasingly been recognized as a key driver of economic growth, social empowerment, and innovation on a global scale. Over the past decades, scholarly interest in this field has expanded significantly, exploring diverse themes from gender equality and socio-cultural barriers to technology adoption and entrepreneurial ecosystems. This study aims to map the intellectual structure, thematic evolution, and collaboration patterns of global women entrepreneurship research through a comprehensive bibliometric analysis. Data were retrieved from the Scopus database without year restrictions, covering peer-reviewed articles, reviews, and conference papers. The dataset was analyzed using VOSviewer to perform performance analysis and science mapping, examining publication trends, prolific authors, leading countries, and keyword co-occurrence networks. The results reveal that economic development, gender equality, and empowerment are central, persistent themes, while emerging topics such as entrepreneurial ecosystem, social media, and motivation indicate a shift toward technology-enabled and ecosystem-based approaches. Collaboration networks highlight the dominance of countries like the United States, United Kingdom, and India, alongside growing contributions from developing economies. This study contributes to the theoretical understanding of women entrepreneurship by consolidating fragmented literature and identifying future research opportunities, offering practical implications for policymakers and development agencies aiming to foster inclusive and sustainable entrepreneurship globally.